General internists of experience suspected variant angina as gastroesophageal reflux diseases in two cases: Heart burn may be related to coronary spasm. Issue 3 (March 2020) - Sueda, Shozo
Abstract: General physicians of experience suspected variant angina as gastroesophageal reflux disease (GERD) due to heart burn in two patients. Proton pump inhibitors were administered in these patients, although spontaneous ST segment elevations were recognized and total or subtotal coronary spasm was provoked by the pharmacological spasm provocation tests. Under the vasodilators but not proton pump inhibitors, two patients complained of neither heart burn nor chest symptoms. General internists and cardiologists should bear in mind coronary spasm when they suspect GERD due to heart burn. Guidelines for GERD may note the necessity of differential diagnosis of coronary artery spasm as one of etiology of GERD-related chest symptoms. <Learning objective: We describe two cases of active variant angina suspected as gastroesophageal reflux disease (GERD) initially by experienced general internists. General physicians and cardiologists should discriminate GERD from coronary spastic angina or Prinzmetal variant angina.>